OF VALUE (VALUELESS, IF NO EXCHANGE CAPACITY) - Pal, Dibakar (European Scientific Journal, ESJ, 2015)
In this paper I consider the question: What is Value? Value means the worth of something in terms of money or other goods for which it can be exchanged: a thing is valuable only when it has exchange capacity. From the point of view of economics a thing is valuable if and only if it can earn or has returning capacity. Return on Investment (ROI) is based on this principle: the more earning the more value, the less earning the less value, no earning, no value. Thus no exchange capacity signifies no value at all. This is a narrow account of value. A mother's affection is a most valuable exchange: recalling this affection with nostalgia renders a man sad by the recollection of the past golden days of childhood. The first smile of a lover is valuable to an emotional heart, so valued that a thousand lovers in the future can hardly compensate for the loss of the warm feeling thus exchanged, that beckoned once to conquer the head and heart of the emotional man rendering him homeless ever after. The value is in the exchange – of money, of goods, of affection – changing our lives.